The roles of an effective supervisor in technical and vocational education and training - Marwa, J. N. (2020)
This paper is focusing on the roles of an effective supervision in TVET. Supervision is designed to promote teaching and learning activities particularly in university, colleges and school. TVET supervisees relay on the instructions of their teachers, instructors and supervisor whom their duty is to teach, direct, advice and guide them in the acquisition of skills, knowledge and attitudes that will make them to become quality graduates after leaving school. However, the study adopted a systematic review approach to search for relevant literatures, TVET supervision, types of supervision in TVET education, Roles of a TVET supervisor, such where the key words used for the selection of the relevant literatures, from data web-based provider such as web of science, Scopus, google scholar and online library. From which the results of the study revealed the appropriate roles of a TVET supervisor in education such as a good relationship process or interpersonal relationship, learning needs, consultation and appointment, experience, training and personality, monitoring and implementation among others. It is therefore recommended that teachers or supervisors should embrace the revealed roles of the study in guiding their supervisees for effectiveness in their career pursuit.